Enterobacteria responsible for urinary infections: a review about pathogenicity, virulence factors and epidemiology - DOUGNON, T. VICTORIEN; ASSOGBA, Phénix; ANAGO, AHOÉFA AMÉLÉ EUGÉNIE (My University, 2020)
Urinary tract infections (UTIs) are one of the most common types of bacterial infections in humans, both in the community and in health care settings. UTIs include a range of clinical entities ranging in severity from asymptomatic infection to acute cystitis, prostatitis, pyelonephritis, and urethritis. This is one of the most common diseases encountered in medical practice today, affecting people of all ages, from newborn to geriatric age group. The bacteria most commonly implicated as agents responsible for UTIs generally originate in the intestine and include Escherichia coli, Pseudomonas spp., Streptococcus spp., Proteus spp., Klebsiella spp., Staphylococcus spp., Neisseria gonorrhoeae, Chlamydia trachomatis, and Candida spp. There are virulence factors of urinary pathogens that promote adhesion to mucosal surfaces and subsequent infections. The multiresistant of these enterobacteria responsible for UTIs is a major public health problem. Antibiotic resistance remains a major problem, especially in the developing countries where hygiene conditions are still precarious and antibiotic use is often abusive and poorly controlled. The multidrug-resistant Enterobacteriaceae most implicated in UTIs by extended-spectrum beta-lactamases (ESBL) and carbapenemase production are: Klebsiella pneumoniae, E. coli, and Proteus spp., not to mention Acinetobacter baumanii and Pseudomonas aeruginosa, the most carbapenemase producing. The detection of ESBL and carbapenemase production is based mainly on phenotypic and genotypic tests.
Keywords: Infections urinaires; Enterobacteriaceae; virulence; multirésistance; BLSE; carbapénémase